Cannabis use frequency, route of administration, and co-use with alcohol among older adults in Washington state - Meenakshi S. Subbaraman; William C. Kerr (BMC, 2021)
Abstract Background The US national surveys and data from legal adult use cannabis states show increases in the prevalence of cannabis use among older adults, though little is known about their manner of cannabis consumption. Here, we examine cannabis use frequency, routes of cannabis administration, and co-use with alcohol, focusing on adults aged 50-64 and ≥65. Methods Data come from a general population survey conducted January 2014-October 2016 (N=5492) in Washington state. We first estimate prevalence and trends in cannabis frequency, routes of administration, and co-use with alcohol in gender by age groups (18-29, 30-49, 50-64, ≥ 65). To test associations between cannabis frequency, route of administration, and co-use with alcohol, we then use sample-weighted multinomial regression adjusted for gender, race/ethnicity, marital status, education, employment, and survey year. Sampling weights are used so results better represent the Washington state population. Regressions focus on the 50-64 and ≥65 age groups. Results Among men and women 50-64, the prevalence of no cannabis use in the past 12 months decreased significantly (84.2% in 2014 to 75.1% in 2016 for women, 76.8% in 2014 to 62.4% in 2016 for men). Among those who report past-year cannabis use, oral administration and vaping and other routes of administration increased by 70% and 94%, respectively each year. Almost one-third of women aged 50-64 and one-fifth of women aged ≥65 who use cannabis reported daily/near daily use, and more than one-third of men who use cannabis in all age groups reported daily/near daily use, including 41.9% of those ≥65. Among men, the prevalence of edibles, drinks, and other oral forms of cannabis administration went up significantly with age (6.6% among 18-29, 21.5% among ≥65). Vaping and other administration are more strongly related to regular and daily/near daily use than infrequent use among those ≥65. The pattern of associations between cannabis frequency and co-use with alcohol differed for women vs. men. Conclusions In a general population representative sample of adults living in a state with legal adult use cannabis, the prevalence of cannabis use increased among those aged 50-64 between 2014 and 2016, the prevalence of daily use is substantial, and oral administration and vaping are increasing.